Pentecostalism : Polyphonic Discourses (Delhi Ayoor, Kerala ISPCK Indian Society for Promoting Christian Knowledge New Life Biblical Seminary, 2019)
Pentecostal/Pentecostalism is a bamboozling term. It is being (mis)interpreted as a denomination, theology, ideology, empiricism, sect, a way of life, movement, and so on. Hence, it is a herculean task to apprehend this multifaceted aspect of Pentecostalism. To expound on this fact, we need profound readings instead of sticking to Particular definition or interpretation. Therefore, we deliberately choose the title- Pentecostalism: Polyphonic Discourses. Through this book, we anticipate to re-imagine holistic consensus on the theoretical and pragmatic framework of Pentecostalism from different perspectives like biblical, theological, historical, ministerial, missiological, sociological and so on. It would penetrate into global Pentecostalism and function as a guideline for further reflections to interface the challenges of the time.
Keywords: Pentecostalism -- India. -- Pentecostal churches -- India. -- Pentecostal churches